Strategies for Media Reform : International Perspectives - McChesney, Robert Waterman, 1952-; Martens, Cheryl, 1972- -; Obar, Jonathan A., -; Freedman, Des, 1962- (Donald McGannon Communication Research Center's Everett C. Parker book series., 2016)
Prepared by thirty-three scholars and activists from more than twenty-five countries, Strategies for Media Reform focuses on theorizing media democratization and evaluating specific projects for media reform. This edited collection of articles offers readers the opportunity to reflect on the prospects for and challenges facing campaigns for media reform and gathers significant examples of theory, advocacy, and activism from multinational perspectives.